Mecanismo de solidificação de ligas do sistema Al-Mn-Ce ricas em Al sob diferentes taxas de resfriamento - Coury, Francisco Gil (Universidade Federal de São Carlos, 2015)
The aircraft industry search for light weight materials to produce lower density parts for increased energy efficiency of fuels was focused in recent years in searching new alloy systems with high mechanical strength and with the ability of producing low-density coatings. The objective of this work was to select a promising system for manufacturing alloys with high mechanical strenght but also capable of forming high hardness samples, for different compositions. The chosen system was mapped in a matter of microstructures formed under different cooling rates, thereby determining the formation region of each phase depending on the cooling rate required for their production. The Al-rich compositions in Al-Mn-Ce system were chosen and their solidification was studied under various cooling rates, from high to low. For high cooling rates, the formation of the crystalline phase Al20Mn2Ce was observed, this is a metastable phase that forms in these Al-rich samples under high cooling rates. The results presented here allow a reinterpretation of the literature data about the phases present in other studies, it is clear that in all cases, the phase present is Al20Mn2Ce, this phase may even coexist with a quasicrystalline phase, the binary Al-Mn quasicrystal, however there is no beneficial effect by adding Ce to the formation of quasicrystals. This phase can also form in copper mold cast samples, in this work produced in the form of cylinders with different diameters, whose yield strength can exceed 800MPa. This phase is relatively thermal stable due to a layer of the Al6Mn phase formed on decomposition of the ternary phase that constitutes a protective cover. Solidification of samples produced under lower cooling rates were also studied. This part of the study enabled the development of a new fraction of the phase diagram of this system.
Keywords: Alumínio; Microscopia eletrônica; Quasicristais; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO